Umur Simpan dan Mutu Sensori Siomay Berbahan Baku Surimi Ikan Tenggiri (Scombereromorus commerson) - Putri, Elis Eka; Harianti, Harianti; Angraeni, Husni (Jurnal Riset Diwa Bahari (JRDB), 2025)
This study aimed to evaluate the shelf life and sensory quality of siomay made from mackerel (Scomberomorus commerson) surimi. The study involved the preparation of siomay using surimi as the main ingredient, followed by sensory evaluation and microbiological analysis to determine the shelf life. The results showed that the sensory quality of siomay decreased with storage time, with significant differences observed in appearance, color, aroma, texture, and taste. These findings suggest that the optimal storage time to maintain sensory quality is within the range of 0 to 12 hours after preparation. This study provides valuable insights for the seafood processing industry regarding the utilization of mackerel surimi in producing high-quality siomay.